The role of autoantibodies in bridging obesity, aging, and immunosenescence - Taylor R. Valentino; Nan Chen; Priya Makhijani; Saad Khan; Shawn Winer; Xavier S. Revelo; Daniel A. Winer (Immunity & Ageing)
Abstract Antibodies are essential to immune homeostasis due to their roles in neutralizing pathogenic agents. However, failures in central and peripheral checkpoints that eliminate autoreactive B cells can undermine self-tolerance and generate autoantibodies that mistakenly target self-antigens, leading to inflammation and autoimmune diseases. While autoantibodies are well-studied in autoimmune and in some communicable diseases, their roles in chronic conditions, such as obesity and aging, are less understood. Obesity and aging share similar aspects of immune dysfunction, such as diminished humoral responses and heightened chronic inflammation, which can disrupt immune tolerance and foster autoantigen production, thus giving rise to autoreactive B cells and autoantibodies. In return, these events may also contribute to the pathophysiology of obesity and aging, to the associated autoimmune disorders linked to these conditions, and to the development of immunosenescence, an age-related decline in immune function that heightens vulnerability to infections, chronic diseases, and loss of self-tolerance. Furthermore, the cumulative exposure to antigens and cellular debris during obesity and aging perpetuates pro-inflammatory pathways, linking immunosenescence with other aging hallmarks, such as proteostasis loss and mitochondrial dysfunction. This review examines the mechanisms driving autoantibody generation during obesity and aging and discusses key putative antigenic targets across these conditions. We also explore the therapeutic potential of emerging approaches, such as CAR-T/CAAR-T therapies, vaccines, and BiTEs, to tackle autoimmune-related conditions in aging and obesity.